Integrating Human Resource Management with Business Strategy: A Literature-Based Analysis - Habibie, Indra; Akbar, Rahmad; Suhailah, Roshikah Wafa; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2024)
The integration of Human Resource Management (HRM) with business strategy has become a critical concern for organizations seeking sustainable competitive advantage in an increasingly dynamic and globalized environment. Strategic Human Resource Management (SHRM) emphasizes the alignment between human capital practices and organizational objectives, positioning employees as strategic assets rather than operational resources. This literature-based analysis synthesizes key theoretical frameworks and empirical findings on the relationship between HRM and business strategy. Drawing exclusively on international peer-reviewed journals, the study examines dominant SHRM models, mechanisms of strategic alignment, and the impact of integrated HRM systems on organizational performance. The analysis reveals that effective integration enhances firm performance through improved employee commitment, capability development, and organizational flexibility. However, the literature also highlights persistent challenges related to implementation, contextual fit, and measurement of HRM outcomes. The study concludes that integrating HRM with business strategy is not a linear or universal process, but a dynamic capability shaped by organizational context, leadership, and external environmental factors.